Radiofrequency Ablation of Liver Tumors - McDermott, Shaunagh; Gervais, Debra A. (Seminars in Interventional Radiology, 2013)
Radiofrequency ablation (RFA) is an alternative therapy for hepatocellular carcinoma and liver metastases when resection cannot be performed or, in the case of hepatocellular carcinoma, when transplant cannot be performed in a timely enough manner to avoid the risk of dropping off the transplant list. RFA has the advantage of being a relatively low-risk minimally invasive procedure used in the treatment of focal liver tumors. This review article discusses the current evidence supporting RFA of liver tumors, as well as the indications, complications, and follow-up algorithms used after RFA.
Keywords: radiofrequency ablation; liver; hepatocellular carcinoma; metastases; technique